Factors Related to Coital Frequency of Women in Their Thirties. Issue 5 (3rd July 2016) - da Silva Lara, Lúcia Alves; dos Santos Lima, Maria Lucia; Romão, Gustavo Salata; Ferriani, Rui Alberto; de Albuquerque Salles Navarro, Paula Andrea
Abstract : This cross-sectional study aimed to identify factors related to coital frequency (CF) among 254 women in their 30s using a semistructured interview to collect sociodemographic, anthropometric, reproductive, clinical, and relationship data. CF was characterized as (a) never, (b) rarely (≤1 times/month), (c) occasionally (≤1 times /week), (d) regularly (2–3 times/week), or (e) frequently (>3 times/week). The mean age was 34.38 ± 0.43 years, mean body mass index (BMI) was 27.86 ± 6.52 kg, mean family income was US1, 044.18 ± 796.19, mean number of children was 1.71 ± 0.89, and mean relationship duration was 8.87 ± 5.11 years. Eighty-seven women (35.2%) were taking hormonal contraceptives, 143 (98.0%) were employed, 239 (96.48%) had a secondary or higher education, and 9 (3.62%) had primary schooling. CF was classified as >3 times/week in 22 (8.66%), 2–3 times/week for 98 (38.58%), ≤1 times/week in 40 (15.75%), ≤1 times/month in 14 (5.51%), and never in 5 (1.97%). Women who reported having coitus >3 times/week a week had significantly higher body mass index (BMI; 32.72 ± 7.42 kg/m 2 ) than those who had coitus 2–3 times/week (28.45 ± 6.76 kg/m 2 ) and ≤1 times /week (26.81 ± 5.39 kg/m 2 ) ( p < 0.01 for both comparisons). Thus, coital frequency varies in women in their 30s. Obese women had a higher CF than normal-weight and overweight women.